The wind in the willows - Grahame, Kenneth, 1859-1932.; Bransom, Paul, 1885- (Stamford, Conn. : Longmeadow Press, 1994)
The escapades of four animal friends who live along a river in the English countryside--Toad, Mole, Rat, and Badger.
Keywords: Animals -- Fiction